The bell tower at the churchyard. A building-historical research into the remains of a late mediaeval bell tower next to the Dutch Reformed church in 's-Heerenberg (Bulletin KNOB, 2001)
In the year 2000 the Dutch Reformed church in 's-Heerenberg was restored, notably the roof of the church was in a bad condition. This opportunity was seized to document various parts of the building, particularly focused on the remains of a large wooden bell tower once standing next to the church. When it was demolished in 1821 much of the old timber was used to hang the bells in the church attic.'s-Heerenberg is a small town in the east of the Netherlands, situated close to the large mediaeval castle Huis Bergh. In 1259 the count Van den Bergh founded a chapel in the place of the present church, which was gradually extended in the course of the Middle Ages and elevated to parish church for the residents of the town in 1399.By the year 1496 the church had acquired such dimensions that on the west side the nave of the church bordered on the castle moat. Consequently, there was no space to build a tower there and this was probably the reason for building a large free-standing bell tower on the north side of the church.As the churchmaster's bill for that year has been preserved, we have a wealth of information on the construction of the tower and the founding of the bells. Three bells were hung in the tower, founded by the renowned bell-founder from Kampen, Geert van Wou.During the Eighty Years' War the church building was severely damaged, but the bell tower seems to have emerged from the battle intact. However, in 1617 it had fallen into ruin to such an extent that it had to be fundamentally restored, to which the town population contributed by means of a collection.